The Relationship Between Nutritional Status and the Development of Children's Cognitive Aspects During the Golden Age (0-6 Years) - Amalya, Meyfa Nur Alfu Laila (Maliki Interdisciplinary Journal, 2024)
Early childhood is an important phase for holistic development, which includes physical, mental and emotional growth. Optimal nutrition plays an important role in supporting cognitive development during this "golden age" (0-6 years). This research explores the relationship between nutritional status and cognitive development of toddlers (0-6 years). Data was collected using qualitative research methods through literature reviews and analysis of relevant sources including journals, articles, books and documents. This research underlines the importance of balanced nutrition in improving cognitive abilities which are important for children's future well-being.